Hepatitis B and C Infection in International Travelers. Issue 3 (4th April 2013) - Johnson, Douglas F.; Leder, Karin; Torresi, Joseph
Abstract : Background: Hepatitis B and C virus (HBV and HCV) cause significant morbidity and mortality worldwide. With the rise in international travel over the last three decades, many travelers are at risk of HBV and HCV infection. Methods: This review focuses on the epidemiology of HBV and HCV in international travelers, the modes of transmission, and the prevention of infection in travelers. Results: The risk of HBV and HCV infection varies widely and depends on the prevalence of the destination country, the duration of travel, and the activities undertaken while abroad. Travelers commonly undertake high‐risk activities that place them at risk of both HBV and HCV infection. Poor uptake of preventative health measures and poor adherence to health recommendations are also common. The monthly incidence of HBV infection for long‐term travelers to endemic countries ranges from 25 to 420 per 100, 000 travelers. HBV infection can be prevented through timely vaccination of travelers. HBV vaccination is safe and efficacious with protective levels of antibodies achieved in >90% of recipients. Information regarding the risk of HCV acquisition is scarce and until recently was limited to case reports following medical interventions. Conclusions: This review demonstrates international travelers are at risk of HBV and HCV infection and provides evidence‐based information enabling health practitioners to provide more appropriate pre‐travel advice. HBV vaccination should be considered in all travelers to countries with a moderate to high HBV prevalence (HBsAg ≥ 2%) and the risk and benefits discussed with the individuals in consultation with the health practitioner. There is no duration of travel without risk of HBV infection. However, it is apparent that those travelers with a longer duration of travel are at greatest risk of HBV infection (ie, expatriates). Travelers should also receive advice regarding the modes of transmission and the activities that place them at risk of both HBV and HCV infection.